‘Life became harder with COVID-19’: exploring the experiences of the COVID-19 pandemic among youth living in eThekwini district, South Africa - (:unkn) unknown (My University, 2024)
Abstract Background In South Africa, pervasive age and gender inequities have been exacerbated by the COVID-19 pandemic and public health response. We aimed to explore experiences of the COVID-19 pandemic among youth in eThekwini district, South Africa. Methods Between December 2021-May 2022 we explored experiences of the COVID-19 pandemic on youth aged 16–24 residing in eThekwini, South Africa. We collated responses to the open-ended question “Has the COVID-19 pandemic affected you in any other way you want to tell us about?” in an online survey focused on understanding the pandemic’s multi-levelled health and social effects. We used a thematic analysis to summarise the responses. Results Of 2,068 respondents, 256 (12.4%, median age = 22, 60.9% women) completed the open-ended survey question (11% in isiZulu). Results were organized into three main themes encompassing (1) COVID-19-related loss, fear, grief, and exacerbated mental and physical health concerns; (2) COVID-19-related intensified hardships, which contributed to financial, employment, food, education, and relationship insecurities for individuals and households; and (3) positive effects of the pandemic response, including the benefits of government policies and silver linings to government restrictions. Conclusions We found that South African youth experienced significant grief and multiple losses (e.g., death, income, job, and educational) during the COVID-19 pandemic. Trauma-aware interventions that provide economic and educational opportunities must be included in post-COVID recovery efforts.
Keywords: African Research